KRITIK HASAN HANAFI TERHADAP FUNDAMENTALISME ISLAM STUDI PEMIKIRAN INTELEKTUAL ARAB PASCA DIFITISME 1967 M - , Yoyo; , Prof. Dr. Heddy Shri-Ahimsa Putra, M.A., M.Phil ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is an effort to analyze and to make a clear mapping on contemporary Arab-Muslim intellectuals thought after the defeat of the Arab- Israeli war in 1967 AD, then known as the âArab Defeatism.â The Six-Day War taking place on June 1967 was disaster for the Arab world and terminated the ideology of Pan-Arab Nationalism and generated the rise of four competing selfcriticism ideologies: Liberal Criticism, Marxist Criticism, Nationalist Criticism, and Fundamentalist Criticism. The ideologies claimed to have their own solutions to the Arab decadence. In this context, Hasan Hanafiâs thought committed to have a real contribution for the Arab-Egyptian future. One of his efforts is to offer a constructive-critique on the problem of Islamic Fundamentalism which he viewed as the last ideology after the failure of secular ideologies. This research has three main questions: (i) How is the trend of Arab- Muslim intellectualâs thought in the Modern Era and after the Arab defeat of 1967 until 2000s? (ii) How is the intellectual background of Hasan Hanafi? (iii) Why Hasan Hanafi criticized Islamic fundamentalism? To what level such critiques addressed? What theories and methodologies he used and how these theories and methodologies have contribution to the problem of Islamic fundamentalism? To answer these three research questions, I offer some theories on Arab intellectualâs thought, thought and ideology relations, and theories on the role of Third World intellectuals (Arab-Muslim). I also used post-colonial approach in a standard meaning that is to reveal every kind of dominations, including religious dogmatism. The works of Hasan Hanafi become main resources and than analyzed by critical reading method, it dose not mean to explain the meaning of the text but on the contrary it intend to produce a new text. This research finally found four major conclusions. First, regarding to the development of contemporary Arab intellectualâs thought, Islamic fundamentalism tends to be a dominant ideology since modern era and after the Arab defeat of 1967. Second, Hasan Hanafi as one of the Arab intellectuals after the Arab defeat, he seems to be a liberal thinker by re-interpreting Islamic heritage (turÄst) as its main feature. Third, Hanafiâs critiques on Islamic fundamentalism do not intend to deconstruct the ideology otherwise he proposed to re-interpret the doctrinal discourse applied by the fundamentalists from Theo-centric thinking to anthropocentric thinking. The last, fundamentalist left or yasÄr al-ushÅ«liyyah proposed by Hanafi not only functioned as a critique but also as a solution to the stagnation of fundamentalist-conservative thinking.